PENGARUH STRATEGI PEMASARAN SYARIAH TERHADAP PENDAPATAN PADA FRANCHISE ES TEH INDONESIA BANDAR LAMPUNG - Yuniar, Halmaita Selvy; Fasa, Muhammad Iqbal (Jurnal Intelek Dan Cendikiawan Nusantara, 2024)
Business competition in Indonesia is getting tighter along with rapideconomic growth and technological developments. Sharia marketingstrategy is one way to face business competition and efforts toincrease product sales. This study was conducted to determine howthe marketing strategy using SWOT analysis in the Indonesian EsTeh Franchise business in Bandar Lampung. The type of researchused is qualitative with a descriptive approach. Data collection techniques use the documentation method. The secondary data from this study were obtained from books, journals and others that refer to the problems and completeness of this study. The results of this study are segmentation, target and positioning strategies carried out so that the marketing strategy is more focused in delivering products to consumers so that it has an impact on increasing sales at theIndonesian Es Teh Franchise in Bandar Lampung